INFLUENCE OF SERVICE EXCELLENCE DIMENSIONS ON GUEST COMPLAINT HANDLING AT PREMIER PLACE HOTEL SURABAYA AIRPORT. - Muhammad Kanza Ramadhino Hermaputra; Damajanti Sri Lestari (International Journal of Multidisciplinary Reseach, 2026)
Strategically located within the Juanda International Airport area, Premier Place Hotel Surabaya Airport faces unique challenges driven by the expectations of transit guests who have high time sensitivity and low error tolerance. In hotel operations, guest complaints cannot be completely avoided, making the effectiveness of complaint handling crucial to maintaining the hotel’s image. This study aims to analyze the effect of Service Excellence dimensions, which consist of Tangibles, Reliability, Responsiveness, Assurance, and Empathy, both partially and simultaneously, on the effectiveness of guest complaint handling. A quantitative approach was employed, utilizing questionnaires distributed to 37 employees (after outlier adjustment) at Premier Place Hotel Surabaya Airport. Data analysis was performed using multiple linear regression. The results indicated that simultaneously, all five dimensions of Service Excellence have a significant effect on complaint handling. Partially, the Reliability, Responsiveness, Assurance, and Empathy dimensions have a positive and significant effect, whereas the Tangibles dimension proved to have no significant effect. These findings provide managerial implications that the hotel needs to focus more on the technical speed and empathetic sensitivity of the staff rather than merely physical attributes when handling guest complaints. Keywords : Service Excellence, Tangibles, Reliability, Responsiveness, Assurance, Empathy, Complaint Handling, Airport Hotel.